Crop residue management in diverse agro-ecosystems for improving soil health- An overview - YADAV, AMBREESH SINGH; ARORA, SANJAY (Journal of Soil and Water Conservation, 2018)
Unavailability of alternative organic amendments, the sustainable management of crop residue in fields can be painstaking key in promoting physical, biological and chemical properties of soil health in agricultural systems of developing countries. There are 140 million ha operational holdings in the country and about 80% are marginal and small farmers. Crop residues of common agricultural crops are important resources, not only as sources of nutrients for succeeding crops, but also for improved air, water and soil quality. Management of crop residues in agriculture can be economically beneficial to many producers and more prominently to farming community. Improved residue management and reduced tillage practices should be encouraged because of their beneficial role in reducing soil degradation and increasing soil productivity. Soil Carbon sequestration contributes to these benefits and can play a significant role in mitigating global climate change. Food security and environmental improvement depend on soil carbon, a valuable resource that can be sustainable in agro-ecosystems through improved and costeffective crop residue management.